Successful Simultaneous Subtotal Splenectomy During Left Lobe Auxiliary Liver Transplantation for Portal Inflow Modulation and Severe Hypersplenism Correction: A Case Report - Zhou, Guang-Peng; Qu, Wei; Zeng, Zhi-Gui; Sun, Li-Ying; Liu, Ying; Wei, Lin; Zhu, Zhi-Jun (Frontiers in Medicine, 2022)
Adult-to-adult living donor liver transplantation with small partial liver grafts often requires intraoperative portal inflow modulation to prevent portal hyperperfusion and subsequent small-for-size syndrome (SFSS). However, there are concerns about the specific morbidity of these modulation techniques. This study aims to lower post-perfusion portal venous pressure and correct severe hypersplenism in a patient with end-stage liver cirrhosis by simultaneous subtotal splenectomy during auxiliary partial orthotopic liver transplantation (APOLT). A 29-year-old man was diagnosed with cryptogenic cirrhosis and severe portal hypertension suffered recurrent acute variceal bleeding, severe thrombocytopenia, and massive ascites before admission to our hospital. After the recipient's left liver was resected, we performed APOLT using his 51-year-old father's left lobe graft with a graft-to-recipient weight ratio of 0.55%. Intraoperatively, simultaneous subtotal splenectomy was performed to lower graft post-perfusion portal vein pressure below 15 mmHg and correct severe hypersplenism-related pancytopenia. The recipient's postoperative hospital course was uneventful with no occurrence of SFSS and procedure-related complications. Platelet and leukocyte counts remained in the normal ranges postoperatively. The living donor was discharged 6 days after the operation and recovered well-with no complications. After a follow-up period of 35.3 months, both the recipient and donor live with good liver function and overall condition. This is the first case report of simultaneous subtotal splenectomy during APOLT using small-for-size living-donated left liver lobes, which is demonstrated to be a viable procedure for modulating portal inflow and correcting severe hypersplenism in selected adult patients with end-stage liver cirrhosis. APOLT using a small-for-size liver graft may be a safe and feasible treatment option for selected adult patients with end-stage liver cirrhosis.